2020
DOI: 10.1007/s12103-020-09559-9
|View full text |Cite
|
Sign up to set email alerts
|

Debt, Incarceration, and Re-entry: a Scoping Review

Abstract: People involved with the criminal justice system in the United States are disproportionately low-income and indebted. The experience of incarceration intensifies financial hardship, including through worsening debt. Little is known about how people who are incarcerated and their families are impacted by debt and how it affects their reentry experience. We conducted a scoping review to identify what is known about the debt burden on those who have been incarcerated and their families and how this impacts their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 64 publications
(108 reference statements)
0
21
0
Order By: Relevance
“…Despite federal initiatives to reinstate Medicaid eligibility upon release, many reentry youths also struggle with accessing healthcare post‐release (Barnert et al., 2020). The US juvenile justice system also imposes legal financial obligations on incarcerated youth so that many accumulate debt during their stay (Harper et al., 2020). The US juvenile correctional facilities therefore often add to the burden of marginalized youth, starkly contrasting the integrated adolescent forensic treatment models employed in the United Kingdom and other high‐income countries (Young, Greer, & Church, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite federal initiatives to reinstate Medicaid eligibility upon release, many reentry youths also struggle with accessing healthcare post‐release (Barnert et al., 2020). The US juvenile justice system also imposes legal financial obligations on incarcerated youth so that many accumulate debt during their stay (Harper et al., 2020). The US juvenile correctional facilities therefore often add to the burden of marginalized youth, starkly contrasting the integrated adolescent forensic treatment models employed in the United Kingdom and other high‐income countries (Young, Greer, & Church, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Most adolescents rely on support from several family domains in navigating these transitions, while youth who are leaving alternative care or juvenile justice institutions often lack support systems. These youth frequently struggle with health problems and comorbidities (Barnert, Sun, Abrams, & Chung, 2020; Beaudry, Yu, Långström, & Fazel, 2021; Jozefiak et al., 2016), debt (Harper et al., 2020), academic attainment, and employment (Vinnerljung & Sallnäs, 2008; Zajac, Sheidow, & Davis, 2015). In a recent meta‐analysis of youth in forensic care from 19 countries, the authors report substantially higher prevalence rates for all mental disorders for detained youth compared with their non‐detained peers and adult detainees (Beaudry et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The United States incarcerates more people than any other country in the world and millions, especially the poor and people of colour people, are under correctional supervision in some form. Incarceration exacerbates social and ethnic inequalities as people who are or have been incarcerated and their families face serious financial challenges that impact food intake [108]. One form of debt in such families stems from the significant costs incurred as a direct result of criminal justice system involvement [109][110][111].…”
Section: Malnutritionmentioning
confidence: 99%
“…Considering attorney type as a proxy for socioeconomic status, a recent analysis of Pennsylvania court records found that persons represented by indigent defense attorneys repaid less of their LFOs than those represented by private counsel, even though they were assessed comparatively lower totals of fines, costs, and restitution (Ward et al 2020). Some have characterized their LFO debts as "insurmountable" and "unpayable" relative to their personal finances and costs of other necessities such as housing, utilities, and food (Harper et al 2021;Shannon et al 2020, p. 276). Interviews with juveniles owing LFOs and their families indicated that non-payment was common and that this debt burden introduced new and substantial challenges to already strapped family finances (Paik and Packard 2019).…”
Section: Factors Affecting Repaymentmentioning
confidence: 99%